Pharmacokinetic Modeling of Morphine’s Effect on Plasma Concentrations of Ticagrelor and Its Metabolite in Healthy Volunteers - Buszko, Katarzyna; Kubica, Krystian; Hobl, Eva-Luise; Adamski, Piotr; Wnuk, Kacper; Jilma, Bernd; Kubica, Jacek (Frontiers in Physiology, 2021)
The aim of this study was to build a mathematical model describing pharmacokinetics of ticagrelor and its active metabolite (AR-C124910XX) in a stable setting with concomitant administration of morphine. The model consists of a set of four differential equations prepared upon the available knowledge regarding the biological processes in pharmacokinetics of ticagrelor. The set of equations was solved numerically using the Runge-Kutta method. The data were obtained in a double-blind, randomized, placebo-controlled, crossover trial. Twenty four healthy volunteers received 180 mg ticagrelor loading dose together with either 5 mg morphine or placebo. Blood samples were analyzed with liquid chromatography tandem mass spectrometry in order to assess plasma concentrations of ticagrelor and AR-C124910XX before ticagrelor loading dose, and thereafter 1, 2, 3, 4 and 6 hours. The model allowed to reproduce the experimental results accurately and led us to conclusions consistent with clinical observations that morphine delays the time of maximum drug concentration and that the morphine effect occurs due to decreased gastrointestinal motility. Based on the model we were able to predict the effect of drug dose on receptor blocking efficacy.